The Effect of the Indihome Spin Off from PT Telkom Indonesia (Persero) and the Merger of Indihome with Telkomsel on TLKM Shares on the IDX and TLK Shares on the NYSE - In'am Widiarma; Tegowati; Anton Eko Yulianto (Journal of Trends Economics and Accounting Research, 2023)
The world of telecommunications in Indonesia cannot be separated from the role of PT Telekomunikasi Indonesia Tbk, as the largest and long-established telecommunications company and has even become a determinant of the development of telecommunications technology in the country. In the past, conventional telephones installed in homes to communicate long distances were the forerunner of a new civilization for the advancement of telecommunications. However, in the middle of 2023, Telkom will release Indihome, aka spin off, Indihome is identical to conventional telephones owned by Telkom. This decision will make the company more effective and efficient and what will be the impact on the capital market, especialy the response of local and foreign investors. This research uses two statistical analysis test methods, namely Mann Whitney and Spearman. Data analysis using SPSS, comparative tests, namely before and after the spinoff. The data object is stock price movements. The results shows that not all management decisions have a positive impact, as can be seen from the response of local and foreign stock investors to the existing sentiment. Referring to the assumption that Indihome joining Telkomsel does not necessarily mean that Singtel's ownership in Telkomsel will disappear even if dilution occurs. Apart from that, Indihome has a large contribution to Telkom, thereby affecting Telkom's revenue in the near future. Although the long-term target of reducing opex and capex can be realized.